Evaluation of the outcome of CT and MR imaging in pediatric patients with bilateral sensorineural hearing loss. (May 2018) - van Beeck Calkoen, E.A.; Merkus, P.; Goverts, S.T.; van de Kamp, J.M.; Mulder, M.F.; Sanchez Aliaga, E.; Hensen, E.F.
Abstract: Objective: To evaluate the clinically relevant abnormalities as visualized on CT and MR imaging in children with symmetric and asymmetric bilateral sensorineural hearing loss (SNHL), in relation to age and the severity of hearing loss. Study design: Retrospective cohort study. Setting: Tertiary referral otology and audiology center. Patients and diagnostic interventions: From January 2006 until January 2016, a total of 207 children diagnosed with symmetric and asymmetric bilateral SNHL were included. They underwent CT and/or MR imaging for the evaluation of the etiology of their hearing loss. Main outcome measures: Radiologic abnormalities associated with SNHL. Results: 302 scans were performed in 207 children (median age of 0.8 years old) with bilateral SNHL. The most frequently identified cause of bilateral SNHL was a malformation of the labyrinth. The combined diagnostic yield of CT and MR imaging was 32%. The diagnostic yield of MR (34%) was considerably higher than that of CT (20%). We found a higher rate of abnormalities in children with profound hearing loss (41%) compared to milder hearing loss (8–29%), and in asymmetric SNHL (52%) compared to symmetric SNHL (30%). Conclusion: Imaging is essential in the etiologic evaluation of children with bilateral SNHL. The highest diagnostic yield is found in children with bilateral asymmetric SNHL or profound SNHL. Based on our findings, MR is the primary imaging modality of choice in the etiological evaluation of children with bilateral SNHL because of its high diagnostic yield.